Characterization of Erv2p and Pdi1p, two thiol oxidoreductases involved in protein disulfide bond formation in the endoplasmic reticulum of Saccharomyces cerevisiae - Vala, Andrea Lages Lino, 1976- (2010)
Tese de doutoramento em Bioquímica (Regulação Bioquímica), apresentada à Universidade de Lisboa através da Faculdade de Ciências, 2008